Technology for Developing Thinking Ability of Students through Problem Education in Primary Education - Kalendarova Zaravshan Kalbaevna (Researchparks Publishing, 2022)
In this article, the fulfillment of the requirements specified in the regulatory documents covering the content of primary education, problem assignment, problem questions, creation of a problem situation, educational and developmental tasks in the course of the lesson, learning-cognitive competences, and the ability to think, their all-round development, in many ways affect the quality of primary education. It will be discussed about the current problems that have risen to the level of state policy today, and the large-scale reforms that are being carried out in connection with bringing up a mentally and physically mature generation.